Studi kasus : Hernia Inguinalis pada Kucing Domestik: Hernia Inguinalis - Apritya, Desty; Bele, Alexander Joharry Leto; Ningsih, Jeni Yunita; Fransiska, Reissa Yunia; Setiawan, Riesal; Febriani, Sylvawiedya Meutia; Kekang, Yosefi Yuanita; Rahman, Muhammad Noor; Widyawati, Ratna (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
Inguinal hernia is a protrusion of abdominal contents through an inguinal canal in the abdominal cavity. A female domestic two months year old kitten found with abdominal enlargement in ventral area and a mass that can be pushed inward. Physical examination and radiographic imaging showed that the cat had an inguinal hernia. Hematology test showed in the normal range. X-Ray examination showed the visceral out of the abdomen but still in the skin. Based on the results of physical and clinical examinations this cat are diagnosed with inguinal hernia with fausta prognosis. Laparotomy is performed to return the organs into the abdomen and closed the hernia ring with simple interrupted pattern, 3.0 absorbable polyglycolic acid. Postoperatively, cefotaxime sodium injection antibiotics were given and then continued with amoxicillin with dose 20 mg/kg BB and mefenamic acid with dose 16 mg/kg BB and nonsteroidal inflammation tolfenamic acid (0,1 ml/kg BB). The incision wound is healing in 7 days after surgery.